Socialization of Inheritance Dispute Resolution to Increase Family Law Awareness in Sukmajaya Subdistrict, Depok City - Arifardhani, Yoyo; Suwarsit, Suwarsit; Abdullah, Ali (IJCS: International Journal of Community Service, 2024)
This study examines the effectiveness of the inheritance dispute resolution socialization program in increasing awareness of family law in Sukmajaya Village, Depok City. Using a qualitative approach with a case study method, this study involved 30 respondents consisting of families experiencing inheritance disputes, community leaders, legal practitioners, and village officials. The results of the study showed a significant increase in public understanding of inheritance law, with an average increase of 44.9% from the initial condition. Positive transformations were seen from the increasing use of family mediation from 5 to 15 cases per quarter, and the decrease in cases ending in court from 12 to 3 cases. This program succeeded in saving dispute resolution costs by up to 75% compared to litigation and contributed to strengthening social harmony. The main challenges faced include the need to develop materials for digital assets and the digital divide in certain age groups. This study recommends the development of structured modules, strengthening the monitoring and evaluation system, and integration with existing community programs for the sustainability of the program in the future.